Haitian Migration to the Bahamas and The Global Compact for Safe, Orderly and Regular Migration: For a Human Rights Analysis - Galy, Karine (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2022)
This article assesses the Bahamas’ implementation of the Global Compact on Safe, Orderly, and Regular Migration adopted in 2018, particularly in light of its human rights provisions generally and migrants specifically. Indeed, this pact, prepared under the auspices of the UN, is the first intergovernmental agreement to propose a global and comprehensive approach to migration. It is intended to be both a complementary instrument and a synthesis of the body of standards available, particularly in terms of protecting the rights of people in a migration situation. The challenge is to propose an approach to migration as a positive factor requiring cooperation at all levels and demanding a strengthening of human rights for migrants. At the domestic level, however, and despite the general impetus in favor of the Pact, States are still attached to migration policies that are not very favorable to the reception of migrants, based in particular on local circumstances, ideological, economic, health, security or management of migratory flows... The Caribbean region is particularly permeable to this approach to immigration, following the example of the Bahamas, for which Haitian migration is above all “a problem”. Indeed, the choice of this country to comply with the provisions of the Pact, comes up against a conception of Haitian migration based on security, detention, and expulsion, without measures respectful of the imperatives of protection that would allow for the identification of persons in need of international protection, including certain Haitian migrants born in the Bahamas.